Genetic Polymorphism of msp1 and msp2 in Plasmodium falciparum Isolates from Côte d’Ivoire versus Gabon - William Yavo; Abibatou Konaté; Denise Patricia Mawili-Mboumba; Fulgence Kondo Kassi; Marie L. Tshibola Mbuyi; Etienne Kpongbo Angora; Eby I. Hervé Menan; Marielle K. Bouyou-Akotet (Journal of Parasitology Research)
Introduction. The characterization of genetic profile of Plasmodium isolates from different areas could help in better strategies for malaria elimination. This study aimed to compare P. falciparum diversity in two African countries. Methods. Isolates collected from 100 and 73 falciparum malaria infections in sites of Côte d’Ivoire (West Africa) and Gabon (Central Africa), respectively, were analyzed by a nested PCR amplification of msp1 and msp2 genes. Results. The K1 allelic family was widespread in Côte d’Ivoire (64.6%) and in Gabon (56.6%). For msp2, the 3D7 alleles were more prevalent (>70% in both countries) compared to FC27 alleles. In Côte d’Ivoire, the frequencies of multiple infections with msp1 (45.1%) and msp2 (40.3%) were higher than those found for isolates from Gabon, that is, 30.2% with msp1 and 31.4% with msp2. The overall complexity of infection was 1.66 (SD = 0.79) in Côte d’Ivoire and 1.58 (SD = 0.83) in Gabon. It decreased with age in Côte d’Ivoire in contrast to Gabon. Conclusion. Differences observed in some allelic families and in complexity profile may suggest an impact of epidemiological facies as well as immunological response on genetic variability of P. falciparum.